2022
DOI: 10.1002/jsfa.11844
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in skin traits in New Zealand lambs

Abstract: BACKGROUND This study explored the genetic variability in the New Zealand sheep population for economically important skin traits. Skins were collected at slaughter from two progeny test flocks, resulting in 725 skins evaluated for grain strain, flatness, crust leather strength and overall suitability for shoe leather. DNA profiles collected from skins post‐slaughter were matched to individual animals using previously collected high‐density genotypes. RESULTS Considerable phenotypic variation for skin traits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similar results were reported on other farm animals, including sheep 3 , rabbit 7 , and cattle 8 . In addition, a recent study on lambs found that the majority of these traits are moderate to highly heritable 9 . However, genetic mutations and associated genes involved in these traits or parameters are less known yet.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported on other farm animals, including sheep 3 , rabbit 7 , and cattle 8 . In addition, a recent study on lambs found that the majority of these traits are moderate to highly heritable 9 . However, genetic mutations and associated genes involved in these traits or parameters are less known yet.…”
Section: Introductionmentioning
confidence: 99%